2019
DOI: 10.1021/acs.nanolett.9b04111
|View full text |Cite
|
Sign up to set email alerts
|

Atomic to Nanoscale Origin of Vinylene Carbonate Enhanced Cycling Stability of Lithium Metal Anode Revealed by Cryo-Transmission Electron Microscopy

Abstract: Batteries using lithium (Li) metal as the anode are considered promising energy storage systems because of their high specific energy densities. The crucial bottlenecks for Li metal anode are Li dendrites growth and side reactions with electrolyte inducing safety concern, low Coulombic efficiency (CE), and short cycle life. Vinylene carbonate (VC), as an effective electrolyte additive in Li-ion batteries, has been noticed to significantly enhance the CE, whereas the origin of such an additive remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 42 publications
7
93
0
Order By: Relevance
“…[ 25 ] As confirmed in different literature reports, the SEI is predominantly or even exclusively comprised of amorphous phase, regardless of the electrolyte in the batteries. [ 26 ] In addition, the crystalline microphases do not concentrate at the surface of metallic Li. In some cases, the crystalline microphases distribute randomly in SEI, whereas in other cases, these microphases concentrate on the outer layer.…”
Section: Chemical Compositions and Structures Of Solid Electrolyte Inmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] As confirmed in different literature reports, the SEI is predominantly or even exclusively comprised of amorphous phase, regardless of the electrolyte in the batteries. [ 26 ] In addition, the crystalline microphases do not concentrate at the surface of metallic Li. In some cases, the crystalline microphases distribute randomly in SEI, whereas in other cases, these microphases concentrate on the outer layer.…”
Section: Chemical Compositions and Structures Of Solid Electrolyte Inmentioning
confidence: 99%
“…A monolithic SEI which was rich in inorganic species was reported very recently. [ 26b ] These inorganic compounds were distributed uniformly in an amorphous state in this SEI. This finding indicates that amorphous SEI indeed exists, but particular electrolyte is needed.…”
Section: Chemical Compositions and Structures Of Solid Electrolyte Inmentioning
confidence: 99%
“…Various electrolyte additives with higher HOMO and lower LUMO energies such as FEC, VC, KNO 3 , LiNO 3 , Li polysulfides (LiPS), or a mixture of them have been designed for Li metal anodes. [83,[134][135][136][137] FEC is an extensively used SEI-adjusting additive in anodes of LIBs (e.g., graphite anode), since it can preferentially form a stable and dense LiF-rich SEI and suppress the exfoliation of graphite. Li et al identified that addition of 10% FEC into standard carbonate-based electrolyte (EC/DEC) can change the structure of SEI on the surface of Li metal anode (from mosaic model to multilayer model) by employing cryo-EM technique.…”
Section: Dft Calculationmentioning
confidence: 99%
“…Similarly, Xu et al discovered that the composition and structure of both electrochemically deposited Li metal (EDLi) and SEI can be changed by adding VC into the electrolyte, thus affecting the electrochemical performance of Li metal anodes (Figure 16a). [134] Moreover, adding a mixture of different additives has also been developed to stabilize the electrode/ electrode interface. Zhang's group.…”
Section: Dft Calculationmentioning
confidence: 99%
See 1 more Smart Citation